Synthesis, characterization and first principle modelling of the MAB phase solid solutions: (Mn1-xCrx)2AlB2 and (Mn1-xCrx)3AlB4. Issue 2 (1st February 2021) - Hanner, Luke A.; Badr, Hussein O.; Dahlqvist, Martin; Kota, Sankalp; Raczkowski, David; Rosen, Johanna; Barsoum, Michel W.
ABSTRACT: The MAB phases are a family of layered ternary transition metal borides, with atomically laminated crystal structures comprised of transition metal boride (M-B) layers interleaved by single, or double, Al (A) layers. Herein, density functional theory is implemented to evaluate the thermodynamic stability of disordered (Mn1-x Crx )2 AlB2, and disordered and ordered (Mn1-x Crx )3 AlB4 quaternaries. The (Mn1-x Crx )2 AlB2 solid solutions were synthesized over the entire range of substitution. A (Mn1-x Crx )3 AlB4 solid solution was produced, on the base of Cr3 AlB4, to form (Mn0.33 Cr0.66 )3 AlB4 . Powder X-ray diffraction shows lattice parameter shifts and unit cell expansions indicative of successful solid solution formations. GRAPHICAL ABSTRACT: UF0001 IMPACT STATEMENT: In this work, first-principles calculations evaluate the stability of (Mn1-x Crx )2 AlB2 and (Mn1-x Crx )3 AlB4 solid solutions. Experimentally, MAB phase solid solutions of (Mn1-x Crx )2 AlB2 and (Mn0.33 Cr0.66 )3 AlB4 are synthesized for the first time.